2022
DOI: 10.4240/wjgs.v14.i2.143
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms predicting prognosis of patients with pathological stages T1N2-3 and T3N0 gastric cancer

Abstract: BACKGROUND Patients with pathological stages T1N2-3 (pT1N2-3) and pT3N0 gastric cancer (GC) have not been routinely included in the target population for postoperative chemotherapy according to the Japanese Gastric Cancer Treatment Guideline, and their prognosis is significantly different. AIM To identify the high-risk patients after radical surgery by analyzing biomarkers and clinicopathological features and construct prognostic models for them. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The nomogram we constructed added SLR and GPR as one of the evaluation factors compared to the traditional TNM staging system. It was demonstrated that elevation of these two factors was associated with poor prognosis in gastric cancer patients, which is consistent with the results of some previous studies [23][24][25][26] . In gastric cancer patients treated with rst-line chemotherapy, some previous studies have shown that SLR and GPR are independent prognostic indicators [27][28] .…”
Section: Discussionsupporting
confidence: 91%
“…The nomogram we constructed added SLR and GPR as one of the evaluation factors compared to the traditional TNM staging system. It was demonstrated that elevation of these two factors was associated with poor prognosis in gastric cancer patients, which is consistent with the results of some previous studies [23][24][25][26] . In gastric cancer patients treated with rst-line chemotherapy, some previous studies have shown that SLR and GPR are independent prognostic indicators [27][28] .…”
Section: Discussionsupporting
confidence: 91%
“…3 Many prognostic models using various nomograms, scoring systems, and artificial intelligence (AI) models, were developed to predict the overall survival of patients after surgery. [4][5][6][7] However, none of these models have been used extensively in clinical practices due to the limited accuracy in predicting the survival of patients in various situations.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that one of the main reasons for the inaccuracy is the limited number of prognostic variables available to build an adequate model. For simplicity and the uniform application of the prognostic models, prior models depended on a few known variables such as the TNM staging system, age, sex, tumour location, tumour histology, and the extent of the surgery 3,6,8 . However, recent studies demonstrated that additional variables could affect patient survival in gastric cancer, such as nutrition, sarcopenia, anaemia, and interval changes in these variables between pre‐operation and post‐operation 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation